Reduced Circulating Levels of miR-433 and miR-133b Are Potential Biomarkers for Parkinson’s Disease - Zhang, Xiong; Yang, Rui; Hu, Bei-Lei; Lu, Pengcheng; Zhou, Li-Li; He, Zhi-Yong; Wu, Hong-Mei; Zhu, Jian-Hong (Frontiers in Cellular Neuroscience, 2017)
Aberrant expression of microRNA (miRNA) in tissues may lead to altered level in circulation. Considerable evidence has suggested that miRNA deregulation is involved in the pathogenesis of Parkinson’s disease (PD). In this study, we screened a set of PD-associated miRNAs and aimed to identify differentially expressed miRNAs in plasma of PD patients and to evaluate their potentiality to serve as PD biomarkers. A total of 95 subjects consisting of 46 sporadic PD cases and 49 controls were recruited. Plasma levels of six miRNAs including miR-433, miR-133b, miR-34b, miR-34c, miR-153 and miR-7 were evaluated using reverse transcribed quantitative PCR, among which we found that miR-34c and miR-7 were below detection limit under our condition. The results showed that levels of circulating miR-433 (P = 0.003) and miR-133b (P = 0.006), but not miR-34b and miR-153, were reduced in PD patients. miR-433 and miR-133b were strongly correlated in both control and PD groups (rs = 0.87 and 0.85, respectively). The correlation between miR-34b and miR-153 expressions was significantly reduced (P < 0.05) in the PD group. Although miR-433 and miR-133b were likely to be functionally complimentary as suggested by Pathway and Gene Ontology analyses, these two miRNAs per se might not be sufficient to predict PD. No correlation was observed between the four miRNAs and age or severity of disease. Collectively, our results demonstrate that circulating miR-433 and miR-133b are significantly altered in PD and may serve as PD biomarkers.